2017
DOI: 10.47197/retos.v0i33.55079
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de la frecuencia cardiaca en competición, entre jugadores de pádel de elite y de categoría nacional Comparison of heartrate between elite and national paddle players during competition)

Abstract: Los objetivos fueron comparar la frecuencia cardiaca (FC) en pulsaciones/minuto (p/min), entre jugadores de pádel de élite y de categoría nacional, y establecer un perfil medio de intensidades de FC, controlando el tiempo de juego y de descanso, para contrastar el esfuerzo realizado por éstos en competición real. Se registró la FC a un total de 14 jugadores de categoría masculina en dos fases. Siete jugadores (31.14 ± 5.9 años) fueron registrados durante los partidos del campeonato del Valencia Pádel Pro Tour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…A total of 231 padel players, men (n = 161) and women (n = 70) of all competition levels participated in the 13 selected studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The competitive level is divided into professional (n = 120), national (n = 40), regional (n = 23) and minors (n = 32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 231 padel players, men (n = 161) and women (n = 70) of all competition levels participated in the 13 selected studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The competitive level is divided into professional (n = 120), national (n = 40), regional (n = 23) and minors (n = 32).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis and synthesis of this review shows six studies with data on the internal load of padel players in different categories (Table 1). All of them register HR Med, with the amateur level being the lowest data recorded for this variable (126.8 ± 10.4 bpm) (20) compared to the data presented by male athletes in the 1st national category (159.1 ± 13.8 bpm) (14). On the other hand, it has been found that the FC Med values vary greatly depending on the study for athletes in the same category.…”
Section: Internal Loadmentioning
confidence: 97%
“…A higher maximum speed when players move to the ball will also require greater braking, which may affect the player’s balance at the moment of hitting [ 52 , 53 ] and increase the probability of making a mistake [ 54 ]. These findings suggest that coaches should consider training conditioning sessions [ 55 57 ] focusing on movements when players serve (specific distance, maximum speed, acceleration and deceleration). Interestingly, if we compare these results to previous studies in doubles tennis, we see that conventional formation prevails in professional tennis, however, Australian and I-formation had higher efficiency, especially in male category [ 57 ] especially when serving next to the lead.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that coaches should consider training conditioning sessions [ 55 57 ] focusing on movements when players serve (specific distance, maximum speed, acceleration and deceleration). Interestingly, if we compare these results to previous studies in doubles tennis, we see that conventional formation prevails in professional tennis, however, Australian and I-formation had higher efficiency, especially in male category [ 57 ] especially when serving next to the lead. Specifically, Kocib et al [ 58 ] pointed out that the men did not use the Australian tactic, and although the I-formation was more effective than the Classical one, a slightly greater use of the conventional tactic prevailed.…”
Section: Discussionmentioning
confidence: 99%
“…The physical demands in padel have been well defined in several studies. They are caused by intermittent efforts that include turns, jumps, accelerations-decelerations, and strokes [1,2,[6][7][8]. However, few works have studied the mental demands caused by padel training or matches.…”
Section: Introductionmentioning
confidence: 99%